Cosmopolitanism beyond the Monolingual Vision. Issue 4 (18th June 2018) - Bielsa, Esperança
Abstract: This article examines how debates on language and democracy have been differently framed within multiculturalist and cosmopolitan frameworks, questioning some of their underlying assumptions and demonstrating a basic continuity with reference to what is approached as the monolingual vision. It then goes on to propose an alternative conception of the language of democracy based on plurilingualism, linguistic hospitality, and translation. Such a conception is not ignorant of the social role of language in the constitution of individual selves and of collective identities, nor does it avoid confronting the politics of language in a highly unequal global space. It recognizes that the grounds of a cosmopolitan democracy can only be built through generalized plurilingual exchanges and sees in the difficulties of understanding and the productive confrontation with the opacity of others and of ourselves the very substance of democracy amongst diversity. This approach also points in the direction of a cosmopolitan sociology that bridges political cosmopolitanism with forms of literary and artistic cosmopolitanism that have remained rather marginal in cosmopolitan thought.